Factors Affecting the Quality of Internship among Public Health Students in Iran: A Narrative Review Study - MoradAli Zareipour; Masoumeh Abazari; Mohammad Saeed Fattahi Ardakani; Mojtaba Jadgal (Pizhūhish dar Āmūzish-i ̒ulūm-i Pizishkī, 2025)
Introduction: Internships play a critical role in shaping students' core skills and professional competencies, often exerting a more marked impact than traditional academic coursework. Throughout this process, students interact with mentors and the environment, gaining experiences that facilitate the application of learned concepts in practical settings. The present study aimed to identify the factors affecting the quality of internships, specially for public health students. Methods: This study employed a narrative review methodology, with research procedures conducted in accordance with the SANRA checklist. To identify relevant literature, a search of Persian and English texts was performed in the following databases: Science Direct, Scopus, ISI, Web of Science, PubMed, SID, MagIran, and Google Scholar search engine covering the period from 2000 to 2023. Studies pertaining to Iran were included. The selection of relevant studies was carried out sequentially, involving the removal of duplicates, followed by screening based on titles, abstracts, and full texts. At the conclusion of the study screening process, the findings from eight articles were included in the data analysis. Results: The findings of these studies indicated that the factors affecting the quality of public health internships include: cohesive planning, appropriate mentor-to-student ratio, incorporation of student feedback, careful attention to practical activity logs, utilization of educational aids, determination of suitable internship duration, clear placement of the internship within a health center subsidiary, regular evaluations at various stages, the provision of training workshops, and effective communication between students and mentors. These factors were categorized into five domains: educational, planning, human resources, logbook, and clinical environment. Conclusion: To enhance the quality of public health internships, cohesive planning and an appropriate mentor-to-student ratio are essential to better address individual student needs. Furthermore, the establishment of effective feedback systems and attention to practical activity logs can contribute to enhanced learning. The provision and updating of educational resources, the implementation of regular workshops, and the strengthening of communication between students and mentors are additional measures that can improve internship quality and the educational experience for students.